2015
DOI: 10.3892/ol.2015.3797
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of receptor tyrosine kinase-like orphan receptor 2 inhibits cell proliferation and colony formation in osteosarcoma cells by inducing arrest in cell cycle progression

Abstract: Abstract. Osteosarcoma (OS) is the most common malignant tumor of the bone, with a high mortality rate and poor prognosis. Receptor tyrosine kinase-like orphan receptor 2 (ROR2) has been reported to be dysregulated in human malignancies. More recently, ROR2 has been demonstrated to promote OS cell migration and invasion. However, the role of ROR2 in the regulation of OS cell proliferation, as well as the underlying molecular mechanism, remains unclear. The present study aimed to investigate the underlying mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
(36 reference statements)
1
18
1
Order By: Relevance
“…However, other factors can induce the cell cycle arrest of osteosarcoma cells. For example, the knockdown of ROR2 in osteosarcoma cells inhibited cell proliferation and colony formation by inducing cell cycle arrest ( 25 ). In addition, it was previously reported that the exogenous expression of miR-497 in human osteosarcoma MG63 cells suppressed cell proliferation, colony formation, migration and invasion, and induced apoptosis and arrest at the G 0 /G 1 phase of the cell cycle ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, other factors can induce the cell cycle arrest of osteosarcoma cells. For example, the knockdown of ROR2 in osteosarcoma cells inhibited cell proliferation and colony formation by inducing cell cycle arrest ( 25 ). In addition, it was previously reported that the exogenous expression of miR-497 in human osteosarcoma MG63 cells suppressed cell proliferation, colony formation, migration and invasion, and induced apoptosis and arrest at the G 0 /G 1 phase of the cell cycle ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…How does Ror2 regulate proliferation of astrocytes? Although Ror2 has been implicated in the regulation of proliferation in several cell types, including NPCs and cancer cells (Endo et al, ; He et al, ; Huang et al, ; Shojima et al, ; Takiguchi et al, ; Wright et al, ; Yu et al, ), the underlying mechanism is still unclear. We show that induced expression of GFAP in reactive astrocytes is not affected by deletion of Ror2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…23 Accumulating evidence further demonstrates that Ror2 is expressed highly in various types of cancer cells, and plays critical roles in regulating proliferation as well as migration and invasion of these cancer cells. [24][25][26][27] In cells stimulated with growth factors or cells harboring mutations in tumor suppressor genes like p53, retinoblastoma protein (Rb) is heavily phosphorylated by activated cyclin-dependent kinases (CDKs), leading to activation of E2F transcription factors to promote the cell cycle progression from G1 to S phase. [28][29][30][31][32][33] It has been shown that the suppressed expression of Ror2 results in reduced G1/S phase transition in astrocytes and cancer cells.…”
mentioning
confidence: 99%
“…[28][29][30][31][32][33] It has been shown that the suppressed expression of Ror2 results in reduced G1/S phase transition in astrocytes and cancer cells. 23,26 However, it remains unclear about the molecular basis of how Ror2 expression is induced in proliferating cells, and how Ror2 regulates the cell cycle progression.…”
mentioning
confidence: 99%